Lifelong cardiovascular care in Turner syndrome: two cases with review of literature - Shun Moriguchi; Yuri Mukoyama; Fumihiko Takizawa; Atsushi Ogawa; Tetsushi Ogawa; Junko Ito; Yukishige Yanagawa; Chinatsu Komiyama; Rieko Niitsu; Tsuyoshi Isojima (Endocrine Journal)
Cardiovascular disease is one of the most important complications in girls and women with Turner syndrome (TS). Although the latest international guideline provides useful suggestions for the management of cardiovascular diseases in TS, some unknown cardiac conditions warrant physicians’ attention and awareness. Here, we have reported two adult cases wherein significant cardiovascular diseases were detected during the transition period. The first case patient was diagnosed with aortic crank deformity and left subclavian artery aneurysm at 14 years based on the report of cardiac catheterization, computed tomography angiography, and cardiac magnetic resonance imaging, which had remained undetected by annual evaluations using transthoracic echocardiography (TTE). This case emphasizes the importance of cardiac reevaluation during the transition period. The second case patient was diagnosed with moderate mitral valve regurgitation (MR) due to mitral valve prolapse at 18 years through TTE, although the first evaluation at 7 years by TTE detected slight MR without any clinical concerns. The condition however progressed to severe MR at 28 years, requiring mitral valvuloplasty. MR is the most common valve disease worldwide, which makes it challenging to comprehend whether the condition is a complication. However, the condition requiring surgery at this age is extremely rare, which implies the possibility of early progression. Because almost all literature on cardiovascular complications in TS is cross-sectional, further information about longitudinal cardiovascular conditions is vital for optimal care for girls and women with TS. The two cases reported in this article provide significant information for improving lifelong cardiovascular health issues in TS.